Experimental response and design of O-connectors for rocking wall systems. (August 2015) - Twigden, K.M.; Henry, R.S.
Abstract: A unique series of nine cyclic tests were performed on energy dissipating O-connectors for use in seismic resisting unbonded post-tensioned rocking wall systems. The effect of the O-connector profile, steel material and welding process for attaching the O-connectors was investigated and two different failure mechanisms were identified. The welding process used to install the O-connector was found to significantly influence the type of failure mechanism and ductility as such a new O-connector profile was developed to overcome this sensitivity. Design equations to estimate the ultimate strength of the O-connector were proposed and used to develop a bilinear force–displacement approximation. Highlights: A series of nine cyclic tests on O-connector seismic dissipaters were performed. Two failure mechanisms were identified and the less desirable eliminated with a novel design. The welding process was found to have a significant effect on O-connector ductility. Previously observed out-of-plane buckling of the O-connector was mitigated with an improved design. A bilinear force–displacement approximation was proposed and validated.